The process of writing a text by using cooperative learning (2005)
This research project was carried out in order to get ninth graders of the departamental school “El Tequendama” involved in their writing tasks and to improve their writing skills, following the process that a professional writer enables students to write cooperatively and reduces their writing anxiety. Cooperative writing enables the participation of students with a mixture of proficiency level, thus providing greater opportunities to make achievements and therefore greater opportunities to be more deeply involved in their writing tasks. Key words: Teaching writing, teaching techniques, students as writers, team work Este proyecto de investigación se llevó a cabo con el propósito de lograr que los estudiantes de noveno grado del colegio departamental “El Tequendama” se comprometieran con sus actividades de escritura y mejoraran sus habilidades escriturales. El reproducir el proceso que un escritor realiza permite a los estudiantes escribir cooperativamente y reduce la ansiedad provocada por el acto de escribir. La escritura cooperativa potencia la participación de estudiantes con niveles bajos de dominio, brindándoles mayores oportunidades de lograr mejores resultados y por tanto mayores oportunidades de comprometerse con sus actividades de escritura. Palabras claves: Enseñanza de la escritura, técnicas de enseñanza, estudiantes escritores, trabajo en equipo